1965
DOI: 10.1121/1.1909534
|View full text |Cite
|
Sign up to set email alerts
|

Theory for Psychophysical Learning

Abstract: A model for psychophysical learning is constructed by imposing some conditioning principles on concepts derived from the theory of signal detectability. The effects of a priori probability, feedback, and practice are derived in part by Monte Carlo simulation and in part by analysis. The theory makes some novel predictions for the effects of these variables, all of which find support in the literature. Some theoretical results are: (a) performance improves with practice; (b) feedback can be detrimental to perfo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
35
0

Year Published

1966
1966
2008
2008

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(37 citation statements)
references
References 0 publications
2
35
0
Order By: Relevance
“…We use this model not as a replacement for SDT (and do not create new measures of sensitivity and bias based on it), but as an extension of classic SDT that can illustrate how different sources of noise may affect measurable statistics. This model incorporates confidence ratings and encapsulates aspects of decision uncertainty present in numerous previous models (see, e.g., Busemeyer & Myung, 1992;Erev, 1998;Kac, 1969;Schoeffler, 1965;Treisman & Williams, 1984), but does so at a level that does not incorporate learning and other trial-by-trial dynamics present in many of these previous models. This simplification allows us to evaluate the role of decision noise in general, independent of the specific assumptions of these theories (i.e., learning scheme, response mapping, criterion sampling/drift, etc.).…”
Section: The Decision Noise Model (Dnm) a Signal Detection Model Withmentioning
confidence: 99%
See 1 more Smart Citation
“…We use this model not as a replacement for SDT (and do not create new measures of sensitivity and bias based on it), but as an extension of classic SDT that can illustrate how different sources of noise may affect measurable statistics. This model incorporates confidence ratings and encapsulates aspects of decision uncertainty present in numerous previous models (see, e.g., Busemeyer & Myung, 1992;Erev, 1998;Kac, 1969;Schoeffler, 1965;Treisman & Williams, 1984), but does so at a level that does not incorporate learning and other trial-by-trial dynamics present in many of these previous models. This simplification allows us to evaluate the role of decision noise in general, independent of the specific assumptions of these theories (i.e., learning scheme, response mapping, criterion sampling/drift, etc.).…”
Section: The Decision Noise Model (Dnm) a Signal Detection Model Withmentioning
confidence: 99%
“…Some theorists have suggested that the decision criterion drifts along a sensory continuum from trial to trial, perhaps in response to error feedback (see, e.g., Kac, 1969). Others have suggested that decision criteria are sampled from a distribution on each trial (e.g., Erev, 1998), and still others have suggested that the observer learns a probabilistic function mapping sensory evidence onto the response (e.g., Schoeffler, 1965). Exactly how noise enters into the decision process is not important for our argument; thus, we aspresent substantial challenges for SDT and are not just complications caused by degenerate criterion placement, as was suggested by Treisman.…”
Section: Mapping From Percept To Responsementioning
confidence: 99%
“…These models, and various special cases of them, can usually be rejected on the basis of subjects' reports of where they move their criteria. Likewise, various probabilistic models, which have no criteria at all, such as Lee's (1971) rnicromatching model and Schoeffler's (1965) directional stimulus generalization model, can be rejected, at least for numer-…”
mentioning
confidence: 99%
“…A number of previous studies have considered the manner in which S categorizes a sample point that came from one of two possible normal probability distributions (Lee, 1963;Lee & Janke, 1964;1965). Such a distribution was called an externally distributed stimulus, since it is analogous to a stimulus such as a tone or attitude statement which is presumed in detection theory and Thurstone theory to give rise internally on each presentation to a sample point from a probability distribution.…”
mentioning
confidence: 99%